Sistem Pemasaran Kerupuk Emping Melinjo Di BUMDes Desa Selubuk Kecamatan Air Napal Bengkulu Utara - Agustina, Mia Tri (Jurnal Kewirausahaan dan Bisnis, 2024)
Melinjo plant is a shrub plant that grows well in the tropics. This plant has a sturdy stem and large leaves and seeds that are shaped like beans. This is due to limited production capacity of emping melinjo and raw materials, affecting emping market opportunities both domestic and export still cannot be met. On a national scale, emping melinjo can still be improved, according to data from the Ministry of Agriculture shows that the yield of melinjo plants in the national market is increasing. When viewed from the percentage, melinjo production in Indonesia fluctuates tend to increase. Understanding Marketing Systems According to Kotler and Lane (2007) in (Lukmandaru &; Istoto, 2016), states that: Marketing is a social process in which there are individuals and groups who get what they need and want by creating, offering, and freely exchanging valuable products with other parties. So what is meant by the marketing system is a collection of institutions that carry out the task of marketing goods, services, ideas, people and environmental factors that influence each other, and shape and influence the relationship between the company and its market. In Selubuk Village itself has not sold Emping Melinjo Products Using Social media, in addition to collecting production results at Village BUMDes, processors also sell directly to collectors, or consumers can also place orders directly to Selubuk Village BUMDes.